1995
DOI: 10.4141/cjas95-008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selection for feedlot gain, breed and age on growth hormone and growth hormone kinetics in bull calves

Abstract: sur les facteurs qui commandent le taux de croissanle. Les veiux Hereford 6taient plus lourds (P <.0,01) a Ia naissance mais les deux races manifestaient un GMQ comparable (P > 0,05) entre la mise base ei le poids corporel.de 450 kg. Dans chaque race, le GMe global 6tait positivemJnt coirdl€ (P < 0,0i) avec le poids ir la naissance. L'alimentation en cours de s6lection n,avait pas d'effet (f > O,bS) sur le GMQ, sur la GH basale, ni sur le volume constant de rdpartition (V,"), la demi-vie (T'r)' le taux de clai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Other authors (Mears and Kozub, 1994) also reported a lack of dietary effects on basal GH concentrations for diets differing in DM digestibility and protein content. In contrast, Cole et al (1988) found that GH concentrations in sheep were higher in low than high energy level diets.…”
Section: Discussionmentioning
confidence: 98%
“…Other authors (Mears and Kozub, 1994) also reported a lack of dietary effects on basal GH concentrations for diets differing in DM digestibility and protein content. In contrast, Cole et al (1988) found that GH concentrations in sheep were higher in low than high energy level diets.…”
Section: Discussionmentioning
confidence: 98%